Using malarial retinopathy to improve the classification of children with cerebral malaria - Lewallen, Susan (2008)
The mechanisms leading to death in cerebral malaria (CM) remain unclear. We compared clinical and laboratory data among children with CM, categorized by ocular fundus findings, to elucidate differences that suggest different underlying pathological processes. From 1999—2005, standard examinations, treatment and record keeping were used for children with a clinical diagnosis of CM. Children were divided into ocular subgroups: normal fundus (N), malarial retinopathy (R), or papilloedema alone (P) and appropriate statistical tests were used to compare clinical and laboratory findings among groups. Eight hundred and eighty children who had eye examinations within 6 h of admission were included in the analysis. The groups differed significantly in case-fatality rates: Group P, 44.4% (95% CI 25.3—63.2), Group R, 18.0% (95% CI 15.6—22.3) and Group N, 7.0% (95% CI 4.2—9.8). There were also significant differences among the groups in blood pressure, prevalence of deep breathing, haematocrit, parasite density, platelet concentration and, among survivors, hours taken to recover from coma. Differences among groups suggest that different underlying pathophysiological processes are operating in children with CM defined by existing criteria. Our proposed classification, by improving the specificity of diagnosis, would enhance consistency among different study sites and prove useful in future research studies.